The Effect Of Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Non-Performing Loan (NPL), and Loan To Deposit Ratio (LDR) Against Return On Asset (ROA) In General Banks In Southeast Asia 2012-2018 - Deni Sunaryo (Ilomata International Journal of Management, 2020)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Non Performing Loan (NPL), dan Loan to Deposit Ratio (LDR) in the Return On Asset (ROA) on the Commercial Banks in Southeast Asia in 2012-2018. The independent variabel used in this study is Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Non Performing Loan (NPL), dan Loan to Deposit Ratio (LDR). The dependent variabel used is Return On Assets (ROA). The methode used in this study uses purposive sempling technique, using scondary and quantitative data. The results of the analysis show that the data used in this study have met the classical assumption test, multiple regression analysis and hypothesis testing using t test an f test and the test the coefficient of determination using SPSS version 23. Based on the results of the study it can be concluded that 1) Capital Adequacy Ratio (CAR) has a positive and significant effect on Return On Asset (ROA). 2) Net Interest Margin (NIM) has a positive and significant effect on Return On Asset (ROA). 3) Non Performing Loan (NPL) no has a positive and significant effect on Return On Asset (ROA). 4) Loan to Deposite Ratio (LDR) has a negative and significant effect on Return On Asset (ROA).